Produção recombinante e caracterização de uma desintegrina da peçonha de Rhinocerophis alternatus (antiga Bothrops alternatus) com atividade antimetastática visando o desenvolvimento de um novo fármaco - Pontes, Carmen Lucia Salla (Universidade Federal de São Carlos, 2011)
This work presents the study of the effects of an RGD disintegrin from Rhinocerophis alternatus (ancient Bothrops alternatus) in key steps of the metastatic cascade. Disintegrins are cysteine-rich peptides, which have several biological activities related to cell-cell interaction and cell adhesion. The correct pairing of disulfide bonds exposes the adhesive motif which confers binding specificity of disintegrins. These molecules selectively blocks the adhesive function of integrins, which directly participate in various physiological and pathological processes. In the first part of this work, we use the DisBa-01, a disintegrin from B.alternatus in fusion with 6 histidines in pET28a expression vector. The DisBa-01 in the flow system inhibited adhesion of B16F10 melanoma cells and platelets to type I collagen and activated the adhesion of B16F10 melanoma cells to type III collagen. In transmigration and adhesion of breast cancer cells MDA-MB-231, the DisBa-01 had the tendency to reduce these stages of metastatic cascade. The disintegrins have been instrumental in the development of molecules with potential therapeutic application and the effects produced by DisBa-01 in this work as well as others from our laboratory, led us in the second part of this work, the production of the disintegrin B.alternatus without the fusion peptide (called ATN) which conferred increased solubility of the disintegrin. ATN was isolated by two molecular exclusions chromatography and ion exchange chromatography and biological characterization was directed to the anti-metastatic effect of this molecule. In this sense, the ATN was unable to promote the adhesion of human erythroleukemia K562 cells, but inhibited the adhesion of tumor cells K562, B16F10 and MDA-MB-231 to fibronectin had no effect in fibroblasts. ATN is not able to detach the fibroblasts adhered to fibronectin but promotes the detachment of K562 and B16F10 cells previously adhered to fibronectin. However, it does not induce fragmentation of cellular DNA, showing no pro-apoptotic effect. In cell proliferation, the ATN has negative effect with 48 hours of incubation with B16F10 tumor cells, but fibroblasts and MDA-MB-231 this effect was not observed. By flow cytometry we observed the interaction of ATN with αvβ3 integrin. The MDA-MB-231 Tx migration was inhibited by ATN and changed the actin cytoskeleton of these cells. However, an increased activity of MMP-9 was observed in MDA-MB-231 treated with ATN and the invasion of MDA-MB-231 was induced by the RGD disintegrin. These results encourage further studies with this disintegrin in seeking the best concentração of the disintegrin, the identification of cytotoxic activity as well as the best method of distribution of this molecule in vivo.
Keywords: Bioquímica; Desintegrina; Bothrops alternatus; Integrinas; Tumores; Metástase; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR